2015
DOI: 10.1186/s40529-015-0083-9
|View full text |Cite
|
Sign up to set email alerts
|

Study on the effect of magnetic field treatment of newly isolated Paenibacillus sp.

Abstract: BackgroundSymbiotic nitrogen fixation in plants occurs in roots with the help of some bacteria which help in soil nitrogen fertility management. Isolation of significant environment friendly bacteria for nitrogen fixation is very important to enhance yield in plants.ResultsIn this study effect of different magnetic field intensity and treatment time was studied on the morphology, physiology and nitrogen fixing capacity of newly isolated Paenibaccilus sp. from brown soil. The bacterium was identified by 16S rDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
2
4
0
1
Order By: Relevance
“…B11. In addition, Li et al (2015) indicated that the treatment of 300 mT for 10 minutes improved Paenibacillus sp. growth.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…B11. In addition, Li et al (2015) indicated that the treatment of 300 mT for 10 minutes improved Paenibacillus sp. growth.…”
Section: Resultsmentioning
confidence: 99%
“…(Fijałkowski et al, 2015) mentioned that the enhancement of bacterial viability may be due to the activation of bacterial metabolic activity that stimulates the growth rate and biofilm formation. Li et al (2015) and Ren et al (2018) revealed that the stimulation of bacterial growth may also due to the increasing of bacterial enzymatic activities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Medan magnet dilaporkan dapat mempengaruhi aktivitas enzim peroxidase, catalase dan superoxide dismutase (Lie, 2015).…”
Section: Pendahuluanunclassified
“…Liang observed increased enzyme secretion and a 1.5-fold promotion of the intracellular lignin peroxidase activity under a 95 mT MF (Tan et al 2020 ). Li demonstrated an increased growth rate and shortened generation time under magnetic treatment, which were caused through increasing enzyme activity by 1.5–2.0-folds (Li et al 2015 ). Therefore, MF bioaugmentation has tremendous potential for biological waste treatment, and it has been applied in waste water treatment recently.…”
Section: Introductionmentioning
confidence: 99%